Penguatan Ekonomi Masyarakat Melalui Pengolahan Belimbing Wuluh Di Desa Berbek Kabupaten Sidoarjo - Jariyah, Ainun (Journal of Islamic Community Development, 2021)
This research explores the strategies for improving the economyof society through the Berbek Village properties. The village assets that they have are in the form of a bund and belimbing wuluh and the societies also have the potential or skills in food processing but the seas sets have not been use dproperly. This research investigates method for improving society's economy through the properties of the Berbek Village. This research uses the ABCD (Asset Bussed Community Development) strategy that has been in effect for two and a half of months. Starting from the initial phase to the transition throughthe empirical stages of Trend and Shift and Leaky Bucket. Theresults of this research suggest (1) the mother group's empowerment strategy, (2) management training to process star fruit into nutritious syrup drinks in collaboration with the grocery store for the marketing process